Analisis Dan Perancangan Sistem Informasi Pemasaran Perumahan Syariah Berbasis Web Pada PT. Lestari Berkah Abadi - Mincarti, Iis; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2020)
PT. Lestari Berkah Abadi does sharia marketing for their housing manually with promotional media through social media, banners, brochures and word of mouth. With this very simple information system make the company less well known by the general public and the sales are not optimal, because the range of marketing is narrow. Moreover, people could not get the information in real time. The purpose of this research is to design information systems according to the development current technologies namely web-based marketing information system. Methods design in this study using UML and generate a draft of the display in the form of a prototype. With the web-based sharia housing marketing information system is expected to provide opportunities for PT. Lestari Berkah Abadi to expand their marketing network, not only limited to the local area, but also can reach the area more broadly for the consumers with internet access.